Energy Power Plant in Electric Power Distribution Systems Equipping With Distance Protection - Hui Hwang Goh; Sy yi Sim; Dahir Khere Diblawe; Mortar Mohamed Ali; Chin Wan Ling; Qing Shi Chua; Kai Chen Goh (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper suggests the theory of distance protection criteria in power distribution systems for power plant generation. Multi-developed countries have energy power plants that placed in remote areas which are far from the grid line. Hence, they should be coupled to the low power transportation systems necessarily. While higher-rating relays are adopted to preserve feeders at power substations, fuses are merely obtainable outside on feeder channel. The safe system process, space protection is dispatched to save feeders. In this review, feeders with distance relays are equipped, together with over-current protection relays and fuses. Energy power plant having distance protection system is designed the implemented system was a 6-MW unit of compressed power energy reproduction. The sample feeder was shortened to be equal four-bus experiment feeder for transmitting resolution. The fault currents have chances adopted to form protecting regions of distance relays. Protection of the power line through the designed power plants for distance relaying can decrease problem in relay location because of the impedance-based location of the distance relay.